INTEGRATED BUDDHIST LEARNING MANAGEMENT WITH THE PHILOSOPHY OF SUFFICIENCY ECONOMY - Vuḍdhissaro (Jaroenrat), Phramaha Aphisit (Journal of Buddhist Education and Research (JBER), 2024)
Thai education is currently facing numerous challenges due to rapid social, economic, and cultural transformations. Learner development can no longer rely solely on academic knowledge but requires an integration of religious values, ethics, and local wisdom to strengthen resilience for sustainable living. This article aims to present an integrated model of Buddhist learning management with the philosophy of sufficiency economy. The framework is based on Buddhist principles such as the Threefold Training (sīla, samādhi, paññā), the Four Noble Truths, and the Four Bases of Accomplishment, together with the core principles of moderation, reasonableness, and resilience, including knowledge and morality as essential conditions. The findings suggest that such integrated learning management fosters a balance between knowledge, critical thinking, and morality in learners. It leads to sustainable learning outcomes, including ethical conduct, social responsibility, and the ability to live according to the sufficiency economy philosophy, which aligns with the vision of human development in the 21st century. The article also provides practical recommendations such as enhancing teacher competency in integrative pedagogy, developing diverse learning media, and promoting collaboration between schools, temples, and communities to advance sustainable and high-quality education.